Inkjet-printed stretchable and low voltage synaptic transistor array - F. Molina-Lopez (Nature Portfolio, 2019)
The development of novel low-cost fabrication schemes for realizing stretchable transistor arrays with applicability in wearable electronics remains a challenge. Here, the authors report skin-like electronics with stretchable active materials and devices processed exclusively from ink-jet printing.